1981
DOI: 10.1111/j.1526-4610.1981.hed2101010.x
|View full text |Cite
|
Sign up to set email alerts
|

5‐Hydroxytryptamine in Platelets of Patients with Muscle Contraction Headache

Abstract: SYNOPSIS 5‐Hydroxytryptamine (5‐HT) was determined in platelets of 23 patients with muscle contraction headache and the results were compared to those obtained in a control group of 20 healthy persons. 5‐HT was observed to be significantly lower in patients with muscle contraction headache as compared to the control group. It is concluded that 5‐HT may be involved in peripheral andor central pain mechanisms of muscle contraction headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
1

Year Published

1982
1982
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 2 publications
1
31
1
1
Order By: Relevance
“…In fact, these drugs have central action, mostly on monoamine metabolism and receptors. (4) Rolb et al 10 recently demonstrated low platelet 5HT in muscle contraction headache similar to that found in migraine patients. (5) Peripheral painful stimulation either by scalp muscle contraction or vasodilation is expected to be associated with increased Morphine-like material in the CSF.…”
Section: Discussionmentioning
confidence: 71%
“…In fact, these drugs have central action, mostly on monoamine metabolism and receptors. (4) Rolb et al 10 recently demonstrated low platelet 5HT in muscle contraction headache similar to that found in migraine patients. (5) Peripheral painful stimulation either by scalp muscle contraction or vasodilation is expected to be associated with increased Morphine-like material in the CSF.…”
Section: Discussionmentioning
confidence: 71%
“…The finding of higher 5-HT platelet content in migraine with aura [18] was not confirmed [15, 21, 23]. Even in tension headache, platelet and plasma 5-HT are not decreased in headache-free period in comparison to control subjects [1215, 19, 21, 2834] (Table 2). Therefore, we can state that a hyposerotonergic status is not present in migraine and tension headache patients in the periphery.…”
Section: Peripheral Studiesmentioning
confidence: 98%
“…Serotonin is critically important in the pathogenesis of both migraine and tension-type headache, with peripheral serotonin levels dropping similarly during headache attacks for both migraine and tension-type headache [28,29]. Currently accepted models of chronic headache postulate that reductions in peripheral serotonin trigger a headache response.…”
Section: Estrogen and Tension-type Headachementioning
confidence: 99%